A putative gene-for-gene relationship between the Erwinia amylovora effector gene eop1 and the FB_Mar12 resistance locus of Malus ×arnoldiana accession MAL0004 - Emeriewen, Ofere Francis; Zetzsche, Holger; Wöhner, Thomas Wolfgang; Flachowsky, Henryk; Peil, Andreas (Frontiers in Plant Science, 2024)
The bacterial pathogen Erwinia amylovora causes fire blight on rosaceous plants, including apples and their wild relatives. The pathogen uses the type III secretion pathogenicity island to inject effector proteins, such as Eop1, into host plants, leading to disease phenotypes in susceptible genotypes. In contrast, resistant genotypes exhibit quantitative resistance associated with genomic regions and/or R-gene-mediated qualitative resistance to withstand the pathogen. In Malus, strong resistance is observed in some wild species accessions, for example, in Malus xarnoldiana accession MAL0004. The resistance locus FB_Mar12, previously identified on linkage group 12 (LG12) of MAL0004, is one of two gene loci in Malus proven to withstand highly virulent North American strains of E. amylovora. This suggests the influence of a major gene, with a few candidate genes proposed within the FB_Mar12 region. In this report, we provide evidence that this gene locus is completely broken down by a mutant strain of the E. amylovora effector protein Eop1 (Δeop1) following artificial shoot inoculations of an ‘Idared’ × MAL0004 F1 progeny set, indicating a gene-for-gene interaction. Interestingly, Δeop1 does not overcome the resistance of the FB_Mar12 donor MAL0004 itself, but only the QTL on LG12, an indication that other resistance factors, possibly QTLs/genes are contributing to the fire blight resistance of MAL0004.